Azathioprine-Induced Hypersensitivity Vasculitis. Issue 4 (14th April 2023) - Sangiorgio, Michael; Bhagwat, Anil; Middleton, Christopher; Davies, Alex
ABSTRACT: Vasculitic skin rash is a rare but known manifestation of azathioprine hypersensitivity reactions, with several published case reports. In this report, we describe the case of a 63-year-old man on azathioprine for autoimmune hepatitis, who developed a delayed systemic hypersensitivity reaction with biopsy-proven vasculitis, approximately 10 months into his treatment. This resolved after azathioprine discontinuation and has not recurred to date after subsequent administration of 6-mercaptopurine. This case highlights the need for continued monitoring for delayed hypersensitivity reactions to azathioprine after initiation of therapy.